ANALYSIS OF NUMERACY LITERACY SKILLS OF FIFTH GRADE ELEMENTARY SCHOOL STUDENTS - Nafi'an, Muhammad Ilman (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
Elementary school numeracy literacy skills play an important role in mathematics learning outcomes, but some studies only reveal quantitatively, so an in-depth analysis of the numeracy literacy skills of elementary school students is needed. this study aims to analyse the numeracy literacy skills of elementary school students. This research uses a descriptive approach, conducted on class V PKBM Quins, Tulungagung as many as 10 students, the selection of subjects is taken based on numeracy literacy skills and the ability to communicate well, from the existing subjects there is one subject who has the best numeracy literacy skills, namely subject N. then the instruments used are numeracy literacy tests, interviews, observation, and documentation. With data analysis, namely data reduction, data presentation, and data verification. While in checking the validity of the research data using source triangulation techniques. The results of this study indicate that students' numeracy literacy skills are as follows. the subject is able to analyse the information contained in the problem, use symbols and numbers and understand in solving the problem. the subject is able to operate well, easily manipulate numbers and symbols, the subject can conclude the results of the analysis and convert them into narrative form.